Mapping Science Process Skills in Biology: A Study on Digestive System Learning - Dea Lufthania Ayuni; Nengsih Juanengsih; Nur Izwani Mohd Shapri (Journal of Natural Science and Integration, 2026)
Science process skills (SPS) play a crucial role in fostering students' scientific reasoning, inquiry abilities, and conceptual understanding in biology. However, SPS development can be inconsistent across indicators, largely due to variations in instructional practices and learning environments. This study examined students’ SPS within the context of the digestive system topic and identified the factors that influence their development. The researchers used a cross-sectional survey design involving 114 Grade 11 science students from three public schools in South Tangerang City, Indonesia, selected through purposive sampling. The researchers collect data through SPS tests and teacher interviews and analyze it descriptively using percentage scores and performance categories. The results showed that overall SPS achievement was in the good category (77%). Performance varies across indicators: predicting (89%), questioning (88%), and hypothesizing (85%) fall into the very good category; classifying (68%) and interpreting (71%) fall into the good category; and communicating (60%) emerges as the weakest indicator. Interviews with teachers indicated that the limited application of inquiry-based learning, coupled with restricted instructional time, has led to inconsistent development of students' Scientific Process Skills (SPS). These findings underscore the considerable impact that instructional design and classroom practices have on SPS outcomes. Therefore, educators need to apply more structured inquiry-based learning and provide explicit training in scientific communication and data interpretation to achieve balanced SPS development. Keywords: science process skills, biology learning, inquiry-based learning, digestive system.